AKT1, AKT2 and AKT3-dependent cell survival is cell line-specific and knockdown of all three isoforms selectively induces apoptosis in 20 human tumor cell lines - Sandra Koseoglu; Zhuomei Lu; C. Chandra Kumar; Paul T. Kirschmeier; Jun Zou (2007)
AbstractAKT is a key serine/threonine kinase in the PTEN/PI3K/AKT pathway1 and activation of AKT is often observed in human cancers. To explore the role of AKT in cell survival in different tumor cells, we tested 20 human tumor cell lines for response to knockdown of AKT by small interference RNA (siRNA) and/or a kinase-dead mutant AKT. siRNA-mediated knockdown of all three AKT isoforms in tumor cell lines led to a reduction of phosphorylation of AKT substrates. Knockdown of AKT resulted in apoptosis in 6 out of 11 tumor cells with activated AKT. In contrast, knockdown of AKT induced apoptosis in 3 out of 9 cell lines with a low level of active AKT. The responsiveness of the cells to knockdown of AKT was not affected by mutational status of p53 but appeared correlated with overexpression of HER2. To assess the role of individual AKT isoforms, five of the cell lines responsive to knockdown of AKT were further characterized. In ZR-75 cells, AKT1 is the predominant isoform responsible for cell proliferation and survival. Conversely, in IGROV1 cells, AKT2 plays a major role in cell proliferation, but no single isoform is essential for cell survival. Thus, the relative importance of the AKT isoforms is cell linespecific. Our data suggest that inhibiting all three AKT isoforms is necessary to elicit maximal apoptotic response in tumor cells, and the level of activated AKT is a favorable but not always reliable biomarker for pre-selection of responsive tumor cell lines to AKT inhibitors.